Kinetic mechanism of Nicotiana tabacum myosin‐11 defines a new type of a processive motor. Issue 1 (17th October 2014) - Diensthuber, Ralph P.; Tominaga, Motoki; Preller, Matthias; Hartmann, Falk K.; Orii, Hidefumi; Chizhov, Igor; Oiwa, Kazuhiro; Tsiavaliaris, Georgios
Abstract : The 175‐kDa myosin‐11 from Nicotiana tabacum ( Nt 175kDa myosin‐11) is exceptional in its mechanical activity as it is the fastest known processive actin‐based motor, moving 10 times faster than the structurally related class 5 myosins. Although this ability might be essential for long‐range organelle transport within larger plant cells, the kinetic features underlying the fast processive movement of Nt 175kDa myosin‐11 still remain unexplored. To address this, we generated a single‐headed motor domain construct and carried out a detailed kinetic analysis. The data demonstrate that Nt 175kDa myosin‐11 is a highduty ratio motor, which remains associated with actin most of its enzymatic cycle. However, different from other processive myosins that establish a high duty ratio on the basis of a rate‐limiting ADP‐release step, Nt 175kDa myosin‐11 achieves a high duty ratio by a prolonged duration of the ATP‐induced isomerization of the actin‐bound states and ADP release kinetics, both of which in terms of the corresponding time constants approach the total ATPase cycle time. Molecular modeling predicts that variations in the charge distribution of the actin binding interface might contribute to the thermodynamic fine‐tuning of the kinetics of this myosin. Our study unravels a new type of a high duty ratio motor and provides important insights into the molecular mechanism of processive movement of higher plant myosins.—Diensthuber, R. P., Tominaga, M., Preller, M., Hartmann, F. K., Orii, H., Chizhov, I., Oiwa, K., Tsiavaliaris, G., Kinetic mechanism of Nicotiana tabacum myosin‐11 defines a new type of a processive motor. FASEB J. 29, 81–94 (2015). www.fasebj.org